Creating a new mobile learning community with podcasting. (17th February 2010) - Seo, Kay Kyeongju; Curran, Andy; Jennings, Nancy A.; Collins, Chris M.
Podcasting is becoming an important content delivery strategy, shaping new mobile learning communities both in live classrooms and in distance learning environments. Students have shown favourable responses to podcasts and some universities now offer formal podcasting initiatives or programs to assist faculty in using the technology. As podcasting is becoming more popular, there is a need to accurately assess the educational potential of the technology and develop effective strategies for supporting a podcast community. This article explores recent developments in podcasting, reports on a recent survey of 137 US students' perceptions of the technology and describes existing support services for podcasting in 50 US universities.